the Pengaruh Video Guided imagery terhadap Penurunan Dismenorea pada Remaja Putri - Destariani, Elvi; Yuniarti, Yuniarti; Widiyanti, Desi (LPPM Hang Tuah Pekanbaru, 2024)
The prevalence of dysmenorrhea experienced by the majority of women of productive age in Indonesia is around 73%, with the incidence of primary dysmenorrhoea being 54.8%. Dysmenorrhea has a significant negative impact on academic performance both at school and during higher education which will affect academic achievement. The research aims to determine the effect of video-guided imagery on the adolescent dysmenorrhoea scale. The research used a quasi-experimental pre-post-one group design. The population in the study were young women who experienced dysmenorrhoea in the PMB area of Bengkulu City with a sample of 30 people taken using a purposive sampling technique. Research data was collected through pre-test and post-test and processed using the SPSS program. The results of data analysis showed: that there was a difference in scores between the pre-test and post-test results and there was an influence of video-guided imagery on reducing dysmenorrhoea in young women in PMB in the Bengkulu City area (p=0.00). It is hoped that video-guided imagery media can be used as an alternative for non-pharmacological pain reduction for every teenager who experiences dysmenorrhoea and trains adolescent cadres to socialize video-guided imagery in the management of dysmenorrhea for young women.